Characterization of extreme maternal morbidity in women treated at the Villa el Salvador Emergency Hospital during 2019 - Yace-Martinez, Jessica (2024)
Objectives: To determine the sociodemographic, obstetric gynecological and obstetric key characteristics of extreme maternal morbidity in women treated at the Villa El Salvador Emergency Hospital during 2019. Material and methods: Quantitative, correlational study with a non-experimental design, corresponding to the 2019 period; We worked with 332 patients identified as Extreme Maternal Morbidity, the data comes from a secondary source in the registry of the Obstetrics and Gynecology Service and the SIS-GalenPlus Computer System (v.10). Results: 68.7% were between 20 and 35 years old, 68.7% had a secondary hight school, 61.4% cohabits, 77.4% were housewives, 76.8% were between 1 at 4 pregnancies, 41.0% had 6 or more prenatal controls, 53.6% required a cesarean section; Regarding obstetric codes, 81.6% were blue codes, 21.1% were red codes, and 7.2% were yellow codes; 52.1% had a hospital stay between 5 to 10 days, 77.1% presented pre-eclampsia / eclampsia, 54.8% required admission to the Intensive Care Unit and 83.1% required some surgical intervention; significant association was observed between number of pregnancies and type of obstetric code, but not between age group and type of obstetric code. Conclusions: Maternal Morbidity characterization found was: 20 - 35 years old, cohabitation, high school, have had 6 or more pre-birth appointments, complications as preeclampsia/eclampsia, 5-10 days hospitalization, admission to the Intensive Care Unit and some surgical intervention.